The role of TACE in the era of immune-targeted therapy for hepatocellular carcinoma: a meta-analysis based on PSM - Li, Jiahao; Xian, Lei; Wang, Xinsen; Liu, Yingnan; Li, Jiarui (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a major global health challenge, with over 50% of patients ineligible for curative treatments at diagnosis. The combination of molecular targeted therapies and immunotherapy has shown promise in improving outcomes for advanced HCC.ObjectiveThis meta-analysis aims to assess the efficacy of combining transarterial chemoembolisation (TACE) with immune-targeted therapies in patients with unresectable HCC.MethodsA systematic review and meta-analysis conforming to PRISMA guidelines were conducted by searching PubMed, Embase, Web of Science, and the Cochrane Library for studies published up to January 5, 2025. Due to the limited clinical evidence, our study exclusively included retrospective studies based on propensity score matching (PSM) analysis that compared the efficacy of TACE in combination with immune-targeted therapy to immune-targeted therapy alone. Key outcomes assessed included objective response rate (ORR), disease control rate (DCR), one-year overall survival (1-OS), one-year progression-free survival (1-PFS), median overall survival (mOS), and median progression-free survival (mPFS).ResultsA total of 9 PSM studies involving 2119 patients were included. The meta-analysis revealed that TACE significantly improved ORR, DCR, 1-OS, and 1-PFS, in addition to extending mOS and mPFS.ConclusionThe findings suggest that the inclusion of TACE in treatment regimens for unresectable HCC notably enhances tumour control and patient survival. This study provides moderate to high-quality evidence supporting the integration of TACE in advanced HCC management, particularly for those patients not meeting standard TACE criteria.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD 42025631817.